1996
DOI: 10.1063/1.472743
|View full text |Cite
|
Sign up to set email alerts
|

Variational transition state theory for electron transfer reactions in solution

Abstract: Classical trajectory and adiabatic channel study of the transition from adiabatic to sudden capture dynamics. III. Dipole-dipole capture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…13, it was demonstrated that the proton transfer in a strongly H‐bonded complex takes place in 20–30 fs whereas the solvent response is delayed by about 50 fs. In such cases, molecular dynamics (MD) simulation or theory based on the Langevin equation analysis15–20 would give us a more realistic description of the solvation effect than the former methods. In the classical MD simulation, however, one has to optimize charge parameters for the reacting solutes separately for all the configurations of interest along the reaction coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…13, it was demonstrated that the proton transfer in a strongly H‐bonded complex takes place in 20–30 fs whereas the solvent response is delayed by about 50 fs. In such cases, molecular dynamics (MD) simulation or theory based on the Langevin equation analysis15–20 would give us a more realistic description of the solvation effect than the former methods. In the classical MD simulation, however, one has to optimize charge parameters for the reacting solutes separately for all the configurations of interest along the reaction coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…A turnover should also be observed when considering the effect of friction on non‐adiabatic transitions. Some progress has been made in the spatial diffusion‐limited regime [92–95] . However, the turnover theory as formulated at present is limited to adiabatic, single‐surface dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Some progress has been made in the spatial diffusion-limited regime. [92][93][94][95] However, the turnover theory as formulated at present is limited to adiabatic, single-surface dynamics. Both theoretical extensions of the turnover theory, as well as numerically exact quantum simulations, would be needed to verify the effect.…”
Section: Discussionmentioning
confidence: 99%
“…The one close to the present approach is the variational transition state theory proposed by Rips and Pollak and others. 24,[40][41][42] They introduced the collective system-bath coordinate, which is characterized by a maximal mean-free path in the vicinity of crossing point. They have also demonstrated that the energy gap coordinate of the two electronic states provides a good description of the ET dynamics in the fast relaxation limit, which is consistent with the present approach, but cannot be appropriate in the strong solvent friction, and that the optimization approach has to be employed to find an effective coordinate.…”
Section: Discussionmentioning
confidence: 99%